Silver enhances hematite nanoparticles based ethanol sensor response and selectivity at room temperature - Garcia-Osorio, Daniel (2021)
Gas sensors are fundamental for continuous online monitoring of volatile organic com-pounds. Gas sensors based on semiconductor materials have demonstrated to be highly competitive, but are generally made of expensive materials and operate at high temperatures, which are draw-backs of these technologies. Herein is described a novel ethanol sensor for room temperature (25◦C) measurements based on hematite (α-Fe2O3 )/silver nanoparticles. The AgNPs were shown to increase the oxide semiconductor charge carrier density, but especially to enhance the ethanol adsorption rate boosting the selectivity and sensitivity, thus allowing quantification of ethanol vapor in 2–35 mg L−1 range with an excellent linear relationship. In addition, the α-Fe2O3/Ag 3.0 wt% nanocomposite is cheap, and easy to make and process, imparting high perspectives for real applications in breath analyzers and/or sensors in food and beverage industries. This work contributes to the advance of gas sensing at ambient temperature as a competitive alternative for quantification of conventional volatile organic compounds. © 2021 by the authors. Li-censee MDPI, Basel, Switzerland.